What's Not Being Shared in Shared Decision‐Making?. (10th July 2013) - Stark, Meredith; Fins, Joseph J.
Abstract What's not to like about shared decision‐making? These programs employ specially crafted decision aids to educate patients about their treatment options and then merge the newly informed patient preferences, both general and treatment‐specific, with guidance from physicians to optimize medical decisions. Sounds great, right? Even better, recent evidence indicates that shared decision‐making programs may also help bend the proverbial cost curve by reducing the use of medical interventions that patients, now properly educated about their options, often say they do not want. The notion that programs to inform and elicit patient choice might also help to align health care delivery with patient preferences for less invasive and therefore less costly treatment options seems the rarest of mutual wins in health care, in which what is best for the individual might also benefit the whole. Yet there has been scant attention to how the goals of patient care and cost‐containment, and perhaps even profitability, coincide or conflict.